Social Governance and Production Transformation Management System in Mining Industry in Indonesia: Toward A Locally Accomodative Energy Policy - Saptomo, Ade (International Journal of Energy Economics and Policy, 2019)
Policies in the energy and mining sectors have been directed solely to massive exploitation by multinational energy companies, solely aimed at increasing economic activity and its contribution to GDP. This liberal energy policy has a real impact on marginalization and the absence of recognition of rights to indigenous groups and surrounding communities over ownership and the possibility of involvement in the mining production process. Although the orientation of liberalism in the energy sector policy is possible because of the huge amount of capital needed to start exploration of a mine, more serious efforts in shifting the paradigm of energy policy to accommodate the interests of local people need to be developed by looking for empirical examples that occur in the field. This paper aims to analyze the legal basis for a paradigm shift in energy policy, with the empirical study in a coal mining in West Sumatra that has been active since Dutch rule in Indonesia. This study took a field study in a coal mine in Sawahlunto, and found that ownership is possible along with the declining market value of a mine when it is run by a large company. Some legal considerations such as the recognition of community land rights, and the transformation of the production process from mechanical to manual are considered as accommodative measures of energy policy to enable people to benefit directly from the wealth of natural resources in their region. The results highlight the need to an accommodative legal policy that considers the socio-cultural aspects of the local community. Keywords: energy policy, social governance, production system, land right, coal mine. JEL Classifications: Q4, Q48 DOI: https://doi.org/10.32479/ijeep.7582